MR findings of forgotten surgical pad in surgical area [Cerrahi̇ alanda unutulan pamuk pedi̇n MR bulgulari] - (:unkn) unknown (My University, 2007)
Foreign body reaction is a specific type of chronic inflammation characterized by granuloma formation. Foreign body granulomas have been reported to cause clinical symptoms anywhere from months to decades after a surgical procedure. Here, we report a case where a forgotten surgical cotton pad was thought to be a tumoral recurrence and the patient underwent craniotomy. In this case report, we emphasize that although it is very rare, granuloma of foreign body reaction can give a false image of tumoral recurrence.
Keywords: Foreign body; Granuloma; Meningioma recurrence